2017
DOI: 10.1002/adfm.201605397
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Semiconducting Polymer Amphiphiles for In Vivo Photoacoustic Imaging

Abstract: Despite the advantages of semiconducting polymer nanoparticles (SPNs) over other inorganic nanoparticles for photoacoustic (PA) imaging, their synthetic method is generally limited to nanoprecipitation, which is likely to cause the issue of nanoparticle dissociation. The synthesis of near‐infrared (NIR) absorbing semiconducting polymer amphiphiles (SPAs) that can spontaneously self‐assemble into homogeneous nanoparticles for in vivo PA imaging is reported. As compared with their counterpart nanoparticles (SPN1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 48 publications
1
91
0
Order By: Relevance
“…To acquire a PA image of tumor with high CNR, the near infrared (NIR) PA probes should exhibit strong NIR absorption and high photothermal conversion efficiency 6-8. Semiconducting molecules including small molecules and polymers, such as perylene diimide (PDI) 9, 10 and polypyrrole 11, have been widely investigated as PA and photothermal agents, due to their high light absorption efficiency and absorption spectra in the NIR region 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…To acquire a PA image of tumor with high CNR, the near infrared (NIR) PA probes should exhibit strong NIR absorption and high photothermal conversion efficiency 6-8. Semiconducting molecules including small molecules and polymers, such as perylene diimide (PDI) 9, 10 and polypyrrole 11, have been widely investigated as PA and photothermal agents, due to their high light absorption efficiency and absorption spectra in the NIR region 12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of grafting density of PEG on the optical properties of SPAs was examined. Four SPAs (SPA1, SPA2, SPA3 and SPA4) with different molecular weights and grafting densities of PEG were synthesized . Poly(2,5‐bis(2‐hexyldecyl)‐3,6‐di(thiophen‐2‐yl)‐2,5dihydropyrrolo[3,4c]pyrrolo‐1,4‐dione‐ alt 9,9‐dioctyl‐9 H ‐fluorene) (PDPPF) was chosen as the backbone because PDPPF derivatives were suitable for both fluorescence and PA imaging.…”
Section: Effect Of Grafting Densitymentioning
confidence: 99%
“…[76] They found that a high PEG grafting density is beneficial for increasing fluorescence quantum yields, reducing reticuloendothelial uptake, and enhancing permeability and the retention effect. For instance, Pu's group also synthesized amphiphilic Pdots by incorporting hydrophilic PEG chains on the polymer backbones.…”
Section: Photoacoustic Imagingmentioning
confidence: 99%